2019
DOI: 10.1088/1361-6633/aae881
|View full text |Cite
|
Sign up to set email alerts
|

Physics with reactor neutrinos

Abstract: Neutrinos produced by nuclear reactors have played a major role in advancing our knowledge of the properties of neutrinos. The first direct detection of the neutrino, confirming its existence, was performed using reactor neutrinos. More recent experiments utilizing reactor neutrinos have also found clear evidence for neutrino oscillation, providing unique input for the determination of neutrino mass and mixing. Ongoing and future reactor neutrino experiments will explore other important issues, including the n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 271 publications
(664 reference statements)
1
56
0
Order By: Relevance
“…Therefore, a proper combination should take into account a common set of nuisance parameters affecting the three experiments at the same time, within a unified analysis framework. A joint analysis might possibly clarify the apparent preference of Double Chooz for higher values of θ 13 [140] as compared with Daya Bay and RENO. Work is in progress towards this (technically difficult but scientifically worthwhile) joint analysis, as testified by dedicated meetings [143,144] and ongoing common activities mentioned, e.g., in [145,146,147].…”
Section: Short-baseline Reactor Neutrinosmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, a proper combination should take into account a common set of nuisance parameters affecting the three experiments at the same time, within a unified analysis framework. A joint analysis might possibly clarify the apparent preference of Double Chooz for higher values of θ 13 [140] as compared with Daya Bay and RENO. Work is in progress towards this (technically difficult but scientifically worthwhile) joint analysis, as testified by dedicated meetings [143,144] and ongoing common activities mentioned, e.g., in [145,146,147].…”
Section: Short-baseline Reactor Neutrinosmentioning
confidence: 97%
“…Among reactor experiments, Daya Bay [135] dominates current bounds on (∆m 2 , θ 13 ), the corresponding uncertainties being a factor ∼ 2.5 smaller than in RENO [141,136] and significantly smaller than in Double Chooz [137] (see also [140]). Recent analyses have shown that the reactor data combination only leads to fractional differences (well below 1σ) in comparison with bounds from Daya Bay data alone [31,33].…”
Section: Short-baseline Reactor Neutrinosmentioning
confidence: 97%
See 1 more Smart Citation
“…There is an ongoing world-wide program of very short baseline (∼10 m) reactor neutrino experiments in search of sterile neutrino oscillations [121,129]. Almost all of these experiments use liquid or solid scintillator detectors at shallow depth constrained by the locations of the reactor complex.…”
Section: Very Short Baseline Reactor Neutrino Detectorsmentioning
confidence: 99%
“…In addition, several other experiments have proposed measuring long-lived particles including neutrinos at the LHC such as FASER [119], which was recently approved and funded, and MATHUSLA [120]. Figure 6: Theν e flux produced f rom the fission chain of the most common nuclear reactor isotopes [121]. The inverse beta decay threshold is indicated by the magenta vertical line.…”
mentioning
confidence: 99%